A Tecnologia de Gênero na análise de documentários: uma análise comparada de obras de Eliza Capai - Tosta Ferreira, Isabela (Cadernos de Gênero e Diversidade, 2025)
Women directors play an important role on how we perceive and understand narratives in documentaries. The feminine approach put into debate raises possibilities about different perspectives, which can address different sensibilities, bringing to light stories that may have been neglected or underrepresented. When constructing the narrative of documentaries, female directors can bring a different perspective to the construction of the characters and stories of the topics covered, whether they are men, women or things. Through their lens, documented stories come to life in a different way, challenging stereotypes and expanding collective understanding of human experiences. Thus, this article seeks to bring the contributions of Teresa De Lauretis, creator of the concept of technology of gender, to analyze the documentary productions Elize Matsunaga: Era uma vez um crime (2021) and Incompatível com a vida (2023), both by the brazilian director Eliza Capai.